IMPLEMENTASI WAWASAN EKONOMI SYARI'AH PADA KEGIATAN EKONOMI MAHASISWA - Reza Hilmy Luayyin; Muhammad Alfi Syahrin; Tuhfatul Janan; Agniz Ruri Ambarwati (JSE: Jurnal Sharia Economica, 2022)
Each student  has different  level of understanding. Most of them have different knowledge, especially in mastering  science of  sharia economics. Sharia economics is very different, of course, from conventional economics.  A lot of  them better understand or are more familiar with conventional-based economic terms.  Sharia  economics or the study of  mu'amalah  still feels unusual to them. The problems that occur to students STAI Muhammadiyah Probolinggo show that there are differences in attitudes and behavior in implementing sharia economic activities with mastery of sharia economic material in class. This study examines extent of  insight and mastery of sharia economics in sharia economics students in each of their economic activities. This study uses a qualitative descriptive method, which is a method that aims to describe the nature of something that is ongoing  in time  the research  conducted  and examines the causes of a symptom. The data collection technique obtained by the author is through observation and interview techniques. This research data obtained  from the first semester of  Islamic  economics students. The results showed that students had a high enthusiasm and curiosity in learning and mastering economics, eager to try something new, especially in the field of  Islamic  economics, most of them wanted to carry out more  Islamic  economic activities, although some still use  Islamic  economics, conventional, wants  to be  more active and learn deeper about sharia economic norms, values, and principles has good economic insight because they understand that conventional banks considered  to have a threat of usury in them even though they are still selected, have insight and knowledge about  Sharia  economics and able to apply it in their daily activities, They still not mastered  Islamic  economics related to more technical matters, such as analyzing business risk and business management. Meanwhile,  the students' implementation of   sharia economic insight that carried  out by students is going well, it  can be  seen from the variety of sharia-based business, inviting the closest family to do business  of sharia-based and starting to carry out activities in sharia banking. Students are also able to  show  the implementation of  basic insights and understanding of high sharia economics because they are able to refrain from spending wealth just for pleasure but the orientation is for their own benefit.